Platelet-rich plasma for immature post-traumatic scars and early keloids: A scoping review - Virgilio Blandón; Alessandro Alvarado; Miguel Borge; Erick Correa; Taylys Leyton; Sofia Gonzalez (PLoS ONE, 2026)
Background Post-traumatic cutaneous scars enter an immature phase after re-epithelialization, characterized by ongoing inflammation and active remodeling. This phase, typically within six months of injury, may allow preventive interventions before pathological scarring develops. Platelet-rich plasma (PRP) has been suggested as a modulator of scar remodeling due to its growth factor content, but its role in immature scars has not been systematically reviewed. Objective To map and summarize the clinical evidence on autologous platelet-containing plasma (ACP), including platelet-rich plasma (PRP), for immature post-traumatic scars and early keloids, and to identify gaps for future research. Methods A scoping review was performed following established frameworks and reporting guidelines. Databases including PubMed/MEDLINE, DOAJ, SciELO, LILACS, and Google Scholar were searched. Studies evaluating ACP or PRP applied to post-traumatic scars within six months post-epithelialization were included. Results Five studies involving 65 patients met inclusion criteria, including randomized trials, observational studies, and case reports. PRP was mainly delivered via intralesional injection. Evidence suggests PRP may improve clinical scar scores and patient-reported outcomes, with no serious adverse events reported. However, studies were heterogeneous in PRP preparation, dosing, timing, and outcome measures. No study was designed to assess PRP as a preventive monotherapy. Conclusions Evidence for PRP in immature post-traumatic scars and early keloids is extremely limited and heterogeneous. While preliminary findings indicate potential benefit and safety, current data are insufficient to support routine preventive use. High-quality, prospective studies are needed to determine whether PRP can influence scar remodeling or prevent pathological scarring.